The Direction of Personnel and its Responsibilities - Dalton, T.P. (Relations industrielles / Industrial Relations, 1953)
SummaryAfter a short historical summary of the evolution of industrial relations and the direction of personnel, the author defines the functions of personnel management. He then points out the particular obligations of the personnel director himself, in regard to the negotiation of collective agreements, the settlement of grievances and the training of employees. In conclusion, the author reminds us of the numerous and important qualities required to fill properly this function of personnel director.